ANALISIS PENGARUH CITRA MEREK, PERSEPSI KUALITAS, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BANDENG PRESTO (Studi kasus pada konsumen di Bandeng Presto Semarang) - Tambunan, Krystia; Widiyanto, Ibnu (Diponegoro Journal of Management, 2012)
The purpose of this study was to determine the effect of Brand Image, Perceived Quality and  price to the buying decision. This study is a descriptive type of research, ie research that describes the objects that relate to decisions of a general nature. Samples used in the study of 100 respondents. In this study using accidental sampling means sampling is that sampling is done by giving a questionnaire to be filled to the consumers who make purchasing decisions on the Bandeng Presto. Data analysis methods used in this study is a descriptive statistical analysis and regression analysis. Descriptive statistical analysis is the interpretation of data obtained in this study and the data processing which is executed by giving descriptions and explanations. Regression analysis include validity and reliability, the classical assumption test, multiple regression analysis, determination of test, test of Goodness of Fit via the F test and t test. The results prove that the three independent variables namely brand image, perceived quality, and price has a positive and significant effect on the dependent variable, namely  Bandeng Presto purchase decision. The results of multiple regression test showed That all independent variables (brand image,  perceived quality, and price) a  positive influence on purchase decisions. The greatest positive influence on purchase decisions Bandeng Presto are on a variable-brand image with a coefficient of 0.478, then the variable  perceived quality with a coefficient of 0.207, while the most influential variables are low that price of the value of the variable coefficient of 0.198.